Zeitgenössische Kunst = Contemporary Art : Auktion 772. (Köln : Kunsthaus Lempertz Köln, 1999)
Albers, Josef ; Alechinsky, Pierre ; Alt, Otmar ; Altenbourg, Gerhard ; Antes, Horst ; Anzinger, Siegfried ; Appel, Karel ; Armleder, John ; Aubertin, Bernard ; Augustin, Edgar ; Bach, Elvira ; Baechler, Donald ; Banana, Charly ; Baselitz, Georg ; Baukhage, Gerd ; Baumgarten, Bodo ; Berke, Hubert ; Bernhard, Franz ; Berrocal, Miguel ; Berthold, Joachim ; Beuys, Joseph ; Bill, Max ; Boetti, Alighiero ; Bömmels, Peter ; Bonato, Victor ; Bott, Francis ; Bowes, David ; Brecht, George ; Breidenbruch, Frank ; Brodwolf, Jürgen ; Buthe, Michael ; Butler, Reg ; Cage, John ; Calder, Alexander ; Calderara, Antonio ; Caramelle, Ernst ; Cavael, Rolf ; Chevalier, Peter ; Chillida, Eduardo ; Christo ; Claisse, Geneviève ; Condo, George ; Copley, William ; Croissant, Michael ; Cruz-Diez, Carlos ; Dahmen, Karl Fred ; Dahn, Walter ; Darboven, Hanne ; Davie, Alan ; Deppe, Gustv ; Dine, Jim ; Disler, Martin ; Dokoupil, Jiri Georg ; Dorazio, Piero ; Dossi, Ugo ; Droese, Felix ; Dufrêne, François ; Emde, Thomas ; Erben, Ulrich ; Fautrier, Jean ; Feldmann, Hans-Peter ; Fernandez, Arman ; Filliou, Robert ; Fischer, Lothar ; Fleck, Ralph ; Fontana, Lucio ; Förg, Gunther ; Frackmann, Harald ; Fuchs, Ernst ; Fussmann, Klaus ; Geiger, Rupprecht ; Gerz, Jochen ; Girke, Raimund ; Goller, Bruno ; Götz, K.O. (Karl Otto) ; Graubner, Gotthard ; Grützke, Johannes ; Hahn, Friedemann ; Hajdu, Etienne ; Hansen, Al ; Haring, Keith ; Hartung, Hans ; Hauser, Erich ; Heerich, Erwin ; Heidelbach, Karl ; Henninger, Manfred ; Herkenrath, Peter ; Hermanns, Ernst ; Herold, Georg ; Hockney, David ; Hödicke, Karl Horst ; Hoehme, Gerhard ; Hofschen, Edgar ; Hrdlicka, Alfred ; Hundertwasser ; Immendorff, Jörg ; Janssen, Horst ; Jochims, Raimer ; Jorn, Asger ; Judd, Donald ; Kalinowski, Horst Egon ; etc.
biografie
Duits
boek